The Concept of Police Justice in Law Enforcement of Minor Criminal Offenses Through Discretion - Koni, Agung Subayu (CV. Strata Persada Academia, 2025)
Law enforcement is the main function of the police in maintaining public order and security. Police often face situations requiring quick and correct decisions, especially in handling minor crimes. Minor crimes require a proportional and fair law enforcement approach. However, there are problems in law enforcement for minor violations, which are often considered less than proportional. This dilemma is made even more complex by the discretionary authority possessed by the police, which allows them to resolve cases outside formal judicial channels. This research aims to identify the justice form from discretion used by the police in law enforcement against minor crimes and analyze the extent to which this discretion reflects the principles of justice. The research method used is normative with a statutory and conceptual approach. The research results show that discretion is essential in law enforcement and helps police work more professionally and flexibly. Applying restorative justice through discretion shows many benefits, such as restoring relationships between perpetrators and victims and reducing police workload. To increase its effectiveness, training and education for the police is needed, as well as clear policy support to ensure the implementation of restorative justice in accordance with the law and human rights standards.